Les espaces fonctionnels : nouveau référentiel de la gestion durable des ressources ? - Stéphane Nahrath; Frédéric Varone; Jean-David Gerber (VertigO)
Since 20 years or so, we assist, mainly under the pressure of sustainability imperatives, to the emergence of new political regulations of the relations between the societies and their environment and more precisely of the social uses of natural resources. These new modes of regulation, empirically noticeable, are characterised by a joint movement of rearticulating sector-specific policy logics, redefining territorial perimeters and pertinent regulation scales as well as of redefining and redistributing resources use rights. This article has for objective to identify and document these different modalities of questioning the existing logics (sectors, institutional territories and property rights) of the public action, then to propose the concept of functional space as an analytical tool allowing to account for alternative formatting of the public action on the one hand and as conceptual framework which could underlie a new political steering of the public action in favour of sustainability on the other hand.